Sweat-absorbent antibacterial fabric and preparation method thereof
Through the blending of seaweed fiber and cotton fibers and nanomontmorillonite treatment, combined with human protein and chloroacetic acid modification, the sweat absorption and antibacterial properties of the fabric are solved, and the tensile properties and antibacterial effects of the fabric are improved, and the growth of mold is prevented.
Patent Information
- Application Number
- CN202411393654.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-10
AI Technical Summary
Fabrics are prone to breeding bacteria after absorbing sweat, leading to mold problems. It is difficult for the existing technology to effectively solve the needs of antibacterial and sweat-absorbing.
The fabric is prepared by blending seaweed fibers and cotton fibers. By combining sodium alginate aqueous solution and nanomontmorillonite, it is wet spinned and shaped, stretched, washed and dried to increase the antibacterial and sweat-absorbing properties of the fabric. And the tensile properties are improved by the modification of human protein and chloroacetic acid.
It achieves good sweat absorption and antibacterial properties of the fabric, and at the same time improves the tensile properties of the fabric, enhances the affinity for water and liquid absorption, and effectively prevents mold from growing.
Smart Images

Figure BDA0005073128690000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of fabric preparation, and in particular to a sweat-absorbing and antibacterial fabric and a preparation method thereof. Background Art
[0002] Fabrics are materials used to make clothing. Most high-quality, high-end fabrics are comfortable to wear, sweat-wicking and breathable, have a crisp drape, are visually noble, and have a soft touch. With the continuous advancement of science and technology, people's living standards have been greatly improved, and people's requirements for the performance of clothing fabrics are getting higher and higher. In addition to paying attention to the color and style of clothing, they are paying more and more attention to the comfort, safety and other functions of clothing.
[0003] When a user exercises while wearing clothes made of fabric, the fabric will absorb sweat produced on the user's skin surface. The sweat will soak into the fabric, which can easily cause bacteria to grow from the center of the fabric, thus causing mold on the clothes. Therefore, there is room for improvement. Summary of the invention
[0004] In order to improve the antibacterial property of fabrics, the present application provides a sweat-absorbing and antibacterial fabric and a preparation method thereof.
[0005] In the first aspect, the present application provides a sweat-absorbing and antibacterial fabric, which adopts the following technical solution: A sweat-absorbing and antibacterial fabric comprises a fabric body, wherein the fabric body comprises seaweed fiber and cotton fiber, and a preparation method of the seaweed fiber comprises the following steps: Ammonium alginate is added into deionized water to obtain sodium alginate aqueous solution, which is then degassed to obtain spinning solution, which is then wet-spun, shaped, stretched, washed and dried to obtain seaweed fiber.
[0006] By adopting the above technical solution, the fabric made by blending seaweed fiber and cotton fiber has good sweat absorption and antibacterial properties. The reasons are as follows: Cotton fibers are natural fibers composed of multiple layers of cellulose polymers. Therefore, cotton fibers are structurally porous and irregular, which enables cotton fibers to store a large amount of water.
[0007] In addition, there are many hydroxyl functional groups on the surface of cotton fibers, which can form hydrogen bonds with water molecules, making the cotton fibers more hydrophilic, thereby making the fabric more sweat-absorbent.
[0008] Seaweed fiber contains some natural antibacterial ingredients, which can effectively inhibit the growth of bacteria and thus play an antibacterial role.
[0009] Therefore, the fabric prepared by blending seaweed fiber and cotton fiber has good sweat absorption and antibacterial properties.
[0010] Preferably, nano-montmorillonite is added during the preparation of the seaweed fiber. The preparation method of the seaweed fiber comprises the following steps: S1, adding nano-montmorillonite into deionized water, dispersing by ultrasonic, and then swelling to obtain a nano-montmorillonite suspension; adding ammonium alginate into deionized water to obtain a sodium alginate aqueous solution; S2. Mixing the sodium alginate aqueous solution and the nano-montmorillonite suspension, stirring them evenly, and then degassing them to obtain a spinning solution. Then, the spinning solution is subjected to wet spinning, and then successively subjected to shaping, stretching, washing, and drying to obtain seaweed fiber.
[0011] By adopting the above technical solution, the nano-montmorillonite is swelled in deionized water, which can effectively increase the interlayer spacing of the nano-montmorillonite, so that sodium alginate can be better inserted into the interlayer spacing of the nano-montmorillonite, thereby making it easier for the nano-montmorillonite and sodium alginate to undergo physical cross-linking reactions, so that the rigid group silica group in the nano-montmorillonite is connected to the sodium alginate macromolecule, and the carboxyl group on the sodium alginate forms an intermolecular hydrogen bond with the hydroxyl group on the nano-montmorillonite, thereby enhancing and toughening the seaweed fiber through the nano-montmorillonite, effectively improving the tensile properties of the fabric.
[0012] Preferably, the modification preparation method of the nano-montmorillonite comprises the following steps: The nano-montmorillonite is added into deionized water, dispersed by ultrasonic, and then a cationic surfactant is added. After being fully stirred and allowed to stand, the modified nano-montmorillonite is obtained by filtering and drying.
[0013] By adopting the above technical solution, the cationic surfactant exchanges ions with the cations between the nano-montmorillonite layers, so that the cationic surfactant can smoothly enter the nano-montmorillonite layers, thereby increasing the interlayer distance of the nano-montmorillonite, reducing the surface energy of the nano-montmorillonite, and further reducing the agglomeration of the nano-montmorillonite.
[0014] Preferably, the mass ratio of the nano-montmorillonite to the cationic surfactant is 1:(0.4-0.6).
[0015] By adopting the above technical solution and controlling the mass ratio of nano-montmorillonite to cationic surfactant within the above range, the agglomeration of nano-montmorillonite can be effectively reduced.
[0016] Preferably, the cationic surfactant is octadecyltrimethylammonium chloride.
[0017] Preferably, human hair protein is added in the preparation process of the seaweed fiber. The preparation method of the seaweed fiber comprises the following steps: S1. Add nano-montmorillonite into deionized water, disperse by ultrasonic, and then swell to obtain a nano-montmorillonite suspension; add ammonium alginate into deionized water to obtain a sodium alginate aqueous solution; add human hair into a sodium hydroxide aqueous solution, heat to react, filter and separate, and collect the filtrate to obtain a human hair protein solution; S2. Mix the sodium alginate aqueous solution and the nano-montmorillonite suspension, stir evenly, add the human hair protein solution, stir evenly, and then degasse to obtain a spinning solution. Then, the spinning solution is subjected to wet spinning, and then subjected to shaping, stretching, washing, and drying in sequence to obtain seaweed fiber.
[0018] By adopting the above technical scheme, hydrogen bonds are formed between human hair protein and calcium alginate molecules, which increases the number of grooves on the surface of the seaweed fiber, increases the specific surface area, and increases the number of water molecules adsorbed on the surface of the seaweed fiber, thereby increasing the liquid absorption of the seaweed fiber. In addition, human hair protein contains a large number of hydrophilic groups, such as hydroxyl, carboxyl and amino groups, which effectively increase the affinity of the seaweed fiber to the aqueous solution, thereby increasing the liquid absorption of the seaweed fiber and further improving the sweat absorption of the fabric.
[0019] Preferably, the mass ratio of the sodium alginate, nano-montmorillonite and human hair is 4:(0.02-0.04):(1.1-1.5).
[0020] By adopting the above technical solution and controlling the mass ratio of sodium alginate, nano-montmorillonite and human hair within the above range, the tensile properties and sweat absorption of the seaweed fiber can be effectively improved.
[0021] Preferably, the modified preparation method of cotton fiber comprises the following steps: S100, adding cotton fiber to a sodium hydroxide aqueous solution, and obtaining alkaline cotton fiber after sufficient reaction; adding chloroacetic acid to deionized water to obtain a chloroacetic acid aqueous solution; S200, mixing the alkaline cotton fiber and the chloroacetic acid aqueous solution, heating for reaction, adding the acetic acid ethanol aqueous solution for neutralization, and then washing and drying in sequence to obtain modified cotton fiber.
[0022] By adopting the above technical scheme, the cotton fiber is modified by chloroacetic acid, so that carboxyl groups are grafted on the surface of the cotton fiber and hydroxyl groups are grafted on the surface of the seaweed fiber, thereby improving the bonding force between the cotton fiber and the seaweed fiber, and then improving the tensile properties of the fabric.
[0023] Preferably, the mass ratio of the cotton fiber to chloroacetic acid is 1:(1.35-1.55).
[0024] By adopting the above technical solution, the mass ratio of cotton fiber to chloroacetic acid is controlled within the above range, which can effectively improve the stability of carboxymethyl cotton fiber.
[0025] In a second aspect, the present application provides a method for preparing a sweat-absorbing and antibacterial fabric as in the first aspect, which adopts the following technical solution: A method for preparing a sweat-absorbing and antibacterial fabric comprises the following steps: The seaweed fiber and cotton fiber are blended and woven to produce a sweat-absorbing and antibacterial fabric.
[0026] In summary, the present application includes at least one of the following beneficial technical effects: 1. Cotton fiber is porous and irregular, which enables it to store a large amount of water; cotton fiber has good hydrophilicity; and seaweed fiber has good antibacterial effect. Therefore, the fabric prepared by blending seaweed fiber and cotton fiber has good sweat absorption and antibacterial properties.
[0027] 2. The cotton fiber is modified by chloroacetic acid, so that carboxyl groups are grafted on the surface of the cotton fiber, and hydroxyl groups are grafted on the surface of the seaweed fiber, thereby improving the bonding force between the cotton fiber and the seaweed fiber, and then improving the tensile properties of the fabric. DETAILED DESCRIPTION
[0028] The present application discloses a sweat-absorbing and antibacterial fabric. The present application is described in detail below in combination with the embodiments and comparative examples. The raw materials involved in the present application can all be obtained commercially.
[0029] Example 1 The sweat-absorbent and antibacterial fabric comprises a fabric body, and the fabric body comprises seaweed fiber and cotton fiber.
[0030] The method for preparing seaweed fiber comprises the following steps: 4 g of ammonium alginate was added to 100 g of deionized water to obtain a sodium alginate aqueous solution, which was then degassed to obtain a spinning solution. The spinning solution was then extruded through a wet spinning machine, placed in a calcium chloride aqueous solution (the mass concentration of the calcium chloride aqueous solution was 5%) at 25°C to form the solution, and then stretched 1.5 times, washed with water, and dried with hot air to obtain seaweed fiber.
[0031] The preparation method of the sweat-absorbing and antibacterial fabric comprises the following steps: The seaweed fiber and cotton fiber are blended and woven to produce a sweat-absorbing and antibacterial fabric.
[0032] The mass ratio of seaweed fiber to cotton fiber is 1:1.2.
[0033] Example 2 The sweat-absorbent and antibacterial fabric comprises a fabric body, and the fabric body comprises seaweed fiber and cotton fiber.
[0034] The method for preparing seaweed fiber comprises the following steps: S1. Add 0.03g of nano-montmorillonite into 10g of deionized water, disperse by ultrasonic for 2h, and then swell for 120h to obtain a nano-montmorillonite suspension; add 4g of ammonium alginate into 100g of deionized water to obtain a sodium alginate aqueous solution; S2. The sodium alginate aqueous solution and the nano-montmorillonite suspension are mixed, stirred evenly, and then subjected to a degassing treatment to obtain a spinning solution. The spinning solution is extruded through a wet spinning machine, and then placed in a calcium chloride aqueous solution (the mass concentration of the calcium chloride aqueous solution is 5%) at 25° C. to be formed, and then stretched 1.5 times, washed with water, and then dried with hot air to obtain seaweed fiber.
[0035] The preparation method of the sweat-absorbing and antibacterial fabric comprises the following steps: The seaweed fiber and cotton fiber are blended and woven to produce a sweat-absorbing and antibacterial fabric.
[0036] The mass ratio of seaweed fiber to cotton fiber is 1:1.2.
[0037] Example 3 The difference between Example 3 and Example 2 is that the modified preparation method of nano-montmorillonite comprises the following steps: 10g of nano-montmorillonite was added into deionized water, and after ultrasonic dispersion for 30 minutes, 4g of cationic surfactant was added, and after being fully stirred for 45 minutes, it was allowed to stand for 10 minutes, and then the precipitate was separated by centrifuge, and the separated precipitate was dried in a vacuum drying oven at a drying temperature of 60°C for 20 hours to obtain modified nano-montmorillonite.
[0038] The cationic surfactant is octadecyltrimethylammonium chloride.
[0039] Example 4 The difference between Example 4 and Example 2 is that the modified preparation method of nano-montmorillonite comprises the following steps: 10g of nano-montmorillonite was added into deionized water, and after ultrasonic dispersion for 30 minutes, 6g of cationic surfactant was added, and after being fully stirred for 45 minutes, the mixture was allowed to stand for 10 minutes, and then the precipitate was separated by centrifuge. The separated precipitate was dried in a vacuum drying oven at a drying temperature of 60°C for 20 hours to obtain modified nano-montmorillonite.
[0040] The cationic surfactant is octadecyltrimethylammonium chloride.
[0041] Example 5 The difference between Example 5 and Example 2 is that the modified preparation method of nano-montmorillonite comprises the following steps: 10g of nano-montmorillonite was added into deionized water, and after ultrasonic dispersion for 30 minutes, 5g of cationic surfactant was added, and after being fully stirred for 45 minutes, it was allowed to stand for 10 minutes, and then the precipitate was separated by centrifuge, and the separated precipitate was dried in a vacuum drying oven at a drying temperature of 60°C for 20 hours to obtain modified nano-montmorillonite.
[0042] The cationic surfactant is octadecyltrimethylammonium chloride.
[0043] Example 6 The difference between Example 6 and Example 5 is that the mass ratio of nano-montmorillonite to cationic surfactant is 1:0.2.
[0044] Example 7 The difference between Example 7 and Example 5 is that the mass ratio of nano-montmorillonite to cationic surfactant is 1:0.8.
[0045] Example 8 The difference between Example 8 and Example 5 is that human hair is further added during the preparation of the seaweed fiber. The preparation method of the seaweed fiber comprises the following steps: S1. Add 0.02g of nano-montmorillonite to 10g of deionized water, disperse by ultrasound for 2h, and then swell for 120h to obtain a nano-montmorillonite suspension; add 4g of ammonium alginate to 100g of deionized water to obtain a sodium alginate aqueous solution; add 1.5g of human hair to a sodium hydroxide aqueous solution (the mass concentration of the sodium hydroxide aqueous solution is 4%) at a bath ratio of 1:20, react at 80°C for 3h, and then separate by filtration, and collect the filtrate to obtain a human hair protein solution; S2. The sodium alginate aqueous solution, the nano-montmorillonite suspension and the human hair protein solution are mixed, stirred evenly, and then subjected to a degassing treatment to obtain a spinning solution. The spinning solution is extruded through a wet spinning machine, and then placed in a calcium chloride aqueous solution (the mass concentration of the calcium chloride aqueous solution is 5%) at 25° C. to be formed, and then stretched 1.5 times, washed with water, and then dried with hot air to obtain seaweed fiber.
[0046] Example 9 The difference between Example 9 and Example 5 is that human hair is further added during the preparation of the seaweed fiber. The preparation method of the seaweed fiber comprises the following steps: S1. Add 0.04 g of nano-montmorillonite to 10 g of deionized water, disperse by ultrasound for 2 h, and then swell for 120 h to obtain a nano-montmorillonite suspension. Add 4 g of ammonium alginate to 100 g of deionized water to obtain a sodium alginate aqueous solution. Add 1.1 g of human hair to a sodium hydroxide aqueous solution (the mass concentration of the sodium hydroxide aqueous solution is 4%) at a bath ratio of 1:20, react at 80°C for 3 h, and then separate by filtration. The filtrate is collected as a human hair protein solution. S2. The sodium alginate aqueous solution, the nano-montmorillonite suspension and the human hair protein solution are mixed, stirred evenly, and then subjected to a degassing treatment to obtain a spinning solution. The spinning solution is extruded through a wet spinning machine, and then placed in a calcium chloride aqueous solution (the mass concentration of the calcium chloride aqueous solution is 5%) at 25° C. to be formed, and then stretched 1.5 times, washed with water, and then dried with hot air to obtain seaweed fiber.
[0047] Example 10 The difference between Example 10 and Example 5 is that human hair is further added during the preparation of the seaweed fiber. The preparation method of the seaweed fiber comprises the following steps: S1. Add 0.03g of nano-montmorillonite to 10g of deionized water, disperse by ultrasound for 2h, and then swell for 120h to obtain a nano-montmorillonite suspension. Add 4g of ammonium alginate to 100g of deionized water to obtain a sodium alginate aqueous solution. Add 1.3g of human hair to a sodium hydroxide aqueous solution (the mass concentration of the sodium hydroxide aqueous solution is 4%) at a bath ratio of 1:20, react at 80°C for 3h, and then separate by filtration. The filtrate is collected as a human hair protein solution. S2. The sodium alginate aqueous solution, the nano-montmorillonite suspension and the human hair protein solution are mixed, stirred evenly, and then subjected to a degassing treatment to obtain a spinning solution. The spinning solution is extruded through a wet spinning machine, and then placed in a calcium chloride aqueous solution (the mass concentration of the calcium chloride aqueous solution is 5%) at 25° C. to be formed, and then stretched 1.5 times, washed with water, and then dried with hot air to obtain seaweed fiber.
[0048] Embodiment 11 The difference between Example 11 and Example 10 is that the mass ratio of sodium alginate, nano-montmorillonite and human hair is 4:0.01:1.3.
[0049] Example 12 The difference between Example 12 and Example 10 is that the mass ratio of sodium alginate, nano-montmorillonite and human hair is 4:0.05:1.3.
[0050] Example 13 Example 13 is different from Example 10 in that the mass ratio of sodium alginate, nano-montmorillonite and human hair is 4:0.03:0.8.
[0051] Embodiment 14 Example 14 is different from Example 10 in that the mass ratio of sodium alginate, nano-montmorillonite and human hair is 4:0.03:1.8.
[0052] Embodiment 15 The difference between Example 15 and Example 10 is that the modified preparation method of cotton fiber comprises the following steps: S100, adding 10 g of cotton fiber to 100 g of sodium hydroxide aqueous solution (the mass concentration of the sodium hydroxide aqueous solution is 30%), reacting at 20° C. for 1 hour to obtain alkaline cotton fiber; adding 13.5 g of chloroacetic acid to 30 g of deionized water to obtain a chloroacetic acid aqueous solution; S200, after mixing the alkaline cotton fiber and the chloroacetic acid aqueous solution, heat to 70°C and react for 50 minutes, then add acetic acid ethanol aqueous solution (the mass concentration of acetic acid ethanol aqueous solution is 70%) for neutralization, then wash with ethanol aqueous solution (the mass concentration of ethanol aqueous solution is 85%) until neutralization, and finally dry in a drying oven at 70°C to obtain modified cotton fiber.
[0053] Example 16 The difference between Example 16 and Example 10 is that the modified preparation method of cotton fiber comprises the following steps: S100, adding 10 g of cotton fiber to 100 g of sodium hydroxide aqueous solution (the mass concentration of the sodium hydroxide aqueous solution is 30%), reacting at 20° C. for 1 hour to obtain alkaline cotton fiber; adding 15.5 g of chloroacetic acid to 30 g of deionized water to obtain a chloroacetic acid aqueous solution; S200, after mixing the alkaline cotton fiber and the chloroacetic acid aqueous solution, heat to 70°C and react for 50 minutes, then add acetic acid ethanol aqueous solution (the mass concentration of acetic acid ethanol aqueous solution is 70%) for neutralization, then wash with ethanol aqueous solution (the mass concentration of ethanol aqueous solution is 85%) until neutralization, and finally dry in a drying oven at 70°C to obtain modified cotton fiber.
[0054] Embodiment 17 The difference between Example 17 and Example 10 is that the modified preparation method of cotton fiber comprises the following steps: S100, adding 10 g of cotton fiber to 100 g of sodium hydroxide aqueous solution (the mass concentration of the sodium hydroxide aqueous solution is 30%), reacting at 20° C. for 1 hour to obtain alkaline cotton fiber; adding 14.5 g of chloroacetic acid to 30 g of deionized water to obtain a chloroacetic acid aqueous solution; S200, after mixing the alkaline cotton fiber and the chloroacetic acid aqueous solution, heat to 70°C and react for 50 minutes, then add acetic acid ethanol aqueous solution (the mass concentration of acetic acid ethanol aqueous solution is 70%) for neutralization, then wash with ethanol aqueous solution (the mass concentration of ethanol aqueous solution is 85%) until neutralization, and finally dry in a drying oven at 70°C to obtain modified cotton fiber.
[0055] Embodiment 18 The difference between Example 18 and Example 17 is that the mass ratio of cotton fiber to chloroacetic acid is 1:1.25.
[0056] Embodiment 18 The difference between Example 18 and Example 17 is that the mass ratio of cotton fiber to chloroacetic acid is 1:1.65.
[0057] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the fabric body includes cotton fibers.
[0058] Performance testing: 1. Antibacterial The fabrics prepared by Examples 1-18 and Comparative Example 1 were sampled, and after washing, bacteria (Staphylococcus aureus) were implanted in each size (50 cm×50 cm), and the samples were tested for antibacterial properties. The test results are recorded in Table 1, where the higher the antibacterial rate, the better the antibacterial effect of the fabric.
[0059] 2. Tensile properties The fabrics prepared by Examples 1-18 and Comparative Example 1 were sampled (50 cm×50 cm), tested with reference to GB / T14343-2008, and the test results were recorded in Table 1, where the higher the breaking strength, the better the tensile properties of the fabric.
[0060] 3. Sweat absorption The fabrics prepared by Examples 1-18 and Comparative Example 1 were sampled (50 cm×50 cm), tested with reference to GB / T5453-1997, and the test results were recorded in Table 1, wherein the higher the water absorption rate, the better the sweat absorption of the fabric.
[0061] Table 1 Data analysis Specifically combining the test results of Example 2 and Example 1, the tensile properties of Example 2 are higher than those of Example 1. The analysis is as follows: the difference between Example 2 and Example 1 is that nano-montmorillonite is added during the preparation of the seaweed fiber, and the nano-montmorillonite has a reinforcing and toughening effect on the seaweed fiber, thereby improving the tensile properties of the fabric.
[0062] Specifically combining the test results of Examples 3-5 and Example 2, the tensile properties of Example 3-5 are higher than those of Example 2. The analysis is as follows: the difference between Example 3-5 and Example 2 is that the nano-montmorillonite is modified by octadecyltrimethylammonium chloride, which effectively reduces the agglomeration of the nano-montmorillonite, thereby improving the strengthening and toughening effect of the nano-montmorillonite on the seaweed fiber, thereby improving the tensile properties of the fabric.
[0063] Specifically combining the test results of Examples 8-10 and Example 5, the sweat absorption of Examples 8-10 is higher than that of Example 5. The analysis is as follows: the difference between Examples 8-10 and Example 5 is that human hair is added during the preparation of the seaweed fiber, and the human hair keratin formed by the human hair not only increases the specific surface area of the seaweed fiber, but also increases the affinity of the seaweed fiber to the aqueous solution, thereby increasing the liquid absorption of the seaweed fiber, and then improving the sweat absorption of the fabric.
[0064] Specifically combining the test results of Examples 15-17 and Example 10, the sweat absorption of Examples 15-17 is higher than that of Example 10. The analysis is as follows: the difference between Examples 15-17 and Example 10 is that the cotton fiber is modified by chloroacetic acid so that carboxyl groups are grafted on the surface of the cotton fiber, thereby improving the bonding force between the cotton fiber and the seaweed fiber, thereby improving the tensile properties of the fabric.
[0065] Specifically combining the test results of Example 1 and Comparative Example 1, the sweat absorption of Example 1 is higher than that of Comparative Example 1. The analysis is as follows: the difference between Example 1 and Comparative Example 1 is that in addition to cotton fiber, seaweed fiber is also contained in the preparation process of the fabric. The seaweed fiber contains natural antibacterial ingredients, which can effectively improve the antibacterial property of the fabric.
[0066] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A sweat-absorbing and antibacterial fabric, characterized in that: The invention comprises a fabric body, wherein the fabric body comprises seaweed fiber and cotton fiber, and a preparation method of the seaweed fiber comprises the following steps: Ammonium alginate is added into deionized water to obtain sodium alginate aqueous solution, which is then degassed to obtain spinning solution, which is then wet-spun, shaped, stretched, washed and dried to obtain seaweed fiber.
2. The sweat-absorbing and antibacterial fabric according to claim 1, characterized in that: Nano-montmorillonite is also added in the preparation process of the seaweed fiber. The preparation method of the seaweed fiber comprises the following steps: S1, adding nano-montmorillonite into deionized water, dispersing by ultrasonic, and then swelling to obtain a nano-montmorillonite suspension; adding ammonium alginate into deionized water to obtain a sodium alginate aqueous solution; S2. Mixing the sodium alginate aqueous solution and the nano-montmorillonite suspension, stirring them evenly, and then degassing them to obtain a spinning solution. Then, the spinning solution is subjected to wet spinning, and then successively subjected to shaping, stretching, washing, and drying to obtain seaweed fiber.
3. The sweat-absorbing and antibacterial fabric according to claim 3, characterized in that: The modified preparation method of the nano-montmorillonite comprises the following steps: The nano-montmorillonite is added into deionized water, dispersed by ultrasonic, and then a cationic surfactant is added. After being fully stirred and allowed to stand, the modified nano-montmorillonite is obtained by filtering and drying.
4. The sweat-absorbing and antibacterial fabric according to claim 3, characterized in that: The mass ratio of the nano-montmorillonite to the cationic surfactant is 1:(0.4-0.6).
5. The sweat-absorbing and antibacterial fabric according to claim 3, characterized in that: The cationic surfactant is octadecyltrimethylammonium chloride.
6. The sweat-absorbing and antibacterial fabric according to claim 3, characterized in that: Human hair is also added during the preparation of the seaweed fiber. The preparation method of the seaweed fiber comprises the following steps: S1. Add nano-montmorillonite into deionized water, disperse by ultrasonic, and then swell to obtain a nano-montmorillonite suspension; add ammonium alginate into deionized water to obtain a sodium alginate aqueous solution; add human hair into a sodium hydroxide aqueous solution, heat to react, and then filter and separate, and collect the filtrate to obtain a human hair protein solution; S2. Mix the sodium alginate aqueous solution and the nano-montmorillonite suspension, stir evenly, add the human hair protein solution, stir evenly, and then degasse to obtain a spinning solution. Then, the spinning solution is subjected to wet spinning, and then subjected to shaping, stretching, washing, and drying in sequence to obtain seaweed fiber.
7. The sweat-absorbing and antibacterial fabric according to claim 6, characterized in that: The mass ratio of the sodium alginate, nano-montmorillonite and human hair is 4: (0.02-0.04): (1.1-1.5).
8. The sweat-absorbing and antibacterial fabric according to claim 1, characterized in that: The modified preparation method of the cotton fiber comprises the following steps: S100, adding cotton fiber to a sodium hydroxide aqueous solution, and after sufficient reaction, obtaining alkaline cotton fiber; adding chloroacetic acid to deionized water to obtain; S200, mixing the alkaline cotton fiber and the mixture, heating for reaction, adding an acetic acid ethanol aqueous solution for neutralization, and then washing and drying in sequence to obtain modified cotton fiber.
9. The sweat-absorbing and antibacterial fabric according to claim 8, characterized in that: The mass ratio of the cotton fiber to chloroacetic acid is 1:(1.35-1.55).
10. A method for preparing the sweat-absorbing and antibacterial fabric according to claim 1, characterized in that: The steps include: The seaweed fiber and cotton fiber are blended and woven to produce a sweat-absorbing and antibacterial fabric.
Citation Information
Patent Citations
Protein and alginate composite fiber and manufacturing method thereof
CN101654813A
Fabricating technique of alginate fiber cloth
CN104947245A
Preparation method of carboxymethyl cellulose cotton
CN105461813A
Preparation method of alginate fiber medical gauze
CN106362192A
Preparation method for composite fiber spunlaced mask base cloth
CN108914389A